PENTINGNYA FILSAFAT PENDIDIKAN DALAM PEMBENTUKAN KARAKTER - Yasmansyah, Yasmansyah; Iswantir, Iswantir (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
Writing this article aims to describe how important educational philosophy is in shaping one's character through education in schools. The method used in this research is library research (library study). Data sources are collected through articles/scientific journals, books, websites, and others, then processed and analyzed using a descriptive qualitative method. The results of the study show that educational philosophy has a function to provide guidance and direction in the development of educational theories into educational science or pedagogy. Meanwhile, character building through education is efforts that are systematically designed and implemented to help students understand the values ​​of human behavior related to God, oneself, fellow human beings, and the environment. Character education involves aspects of knowledge, feelings and actions. When these three things go hand in hand, it will shape a person's character, which can be good or bad.